ANALISIS HUBUNGAN KECERDASAN EMOSIONAL TERHADAP MOTIVASI PRESTASI OLAHRAGA PADA MAHASISWA ILMU KEOLAHRAGAAN UNIVERSITAS NEGERI SEMARANG - Faqih Meida Rahman; Anies Setiowati (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA (UTP), 2026)
Emotional intelligence is an important part of helping athletes and sports science students manage psychological pressure, increase motivation, and maintain concentration, which has a positive impact on athletic performance. This study employs a quantitative descriptive research design using a questionnaire as the research method. The research subjects are sports science students at Semarang State University. The sample consists of 109 active sports science students at Semarang State University, selected using purposive sampling techniques in accordance with the criteria for sample selection. The research data was obtained from the number of items distributed on the emotional intelligence variable, which consisted of 21 items, and the sports performance motivation variable, which consisted of 9 items. The results of this study showed a linearity deviation significance value of 0.287, an emotional intelligence correlation value with an average of 69.19, and a correlation coefficient value of 0.665 with significance of 0.000. Meanwhile, sports achievement motivation had an average of 30.40, and a correlation coefficient of 0.665 with a significance of 0.000. The study showed that emotional intelligence had a high level of emotional intelligence at 79.8% and a high level of sports achievement motivation at 89.9%. The results of the study indicate that there is a significant relationship between emotional intelligence and sports achievement motivation.